Distribution and source of organic matter in surface sediment from the muddy deposit along the Zhejiang coast, East China Sea. Issue 1 (15th October 2017) - Xu, Gang; Liu, Jian; Hu, Gang; Jonell, Tara N.; Chen, Lilei
Abstract: To constrain organic matter compositions and origins, elemental (TOC, TN, C/N) and stable carbon (δ 13 C) and nitrogen isotope (δ 15 N) compositions are measured for surface sediments collected from muddy deposit along the Zhejiang coast, East China Sea. The results showed that the TOC, TN, C/N, δ 13 C, and δ 15 N were 0.19–0.67%, 0.03–0.09%, 6.76–9.22, − 23.43 to − 20.26‰, and 3.93–5.27‰, respectively. The δ 13 C values showed that the mixing inputs of terrigenous and marine organic matter generally dominated sedimentary organic matter in the west part, and the sedimentary organic matters were mainly influenced by the marine organic matter in the east part of the study area. A stable carbon isotope two end member mixing model estimates ~ 38% terrestrial -derived and ~ 62% marine-derived inputs to sedimentary organic matter. Microbial mineralization strongly controls δ 15 N values, and therefore cannot be used to identify the provenance of organic matter for the Zhenjiang coast. Highlights: δ 13 C could effectively identify the provenance of sedimentary organic matter. Terrigenous organic matter dominated sedimentary organic matter in the west part. Marine organic matter was mainly from the algal cells in the east part.